Appraising sociotechnical visions of sustainable energy futures: A distributed deliberative mapping approach. (March 2022) - Bellamy, Rob; Chilvers, Jason; Pallett, Helen; Hargreaves, Tom
Abstract: Meeting international targets to limit climate change requires countries around the world to decarbonise whole energy systems. It is increasingly recognised that low-carbon energy transitions will need to focus as much on social transformations and the meaningful engagement of society as they do technical aspects. Most existing studies to engage society with energy system change focus on discrete forms of participation around specific technologies or particular parts of the energy system, with very few exploring distributed engagements with energy in terms of 'whole system' change. We set out to address this research gap in two important ways. First, we report on an innovative approach to opening up diverse issue framings and participant perspectives about energy futures in the UK, called distributed deliberative mapping (DDM), that examines how alternative formats and models of public participation shape appraisal outcomes. In this way, we experimentally broaden out beyond conventional deliberative formats of participation, in terms of 'representative' mini-publics and expert elicitation, to also engage with activist, grassroots innovator and consumer-based models of participation and their associated publics. Second, in doing so we develop an explicitly sociotechnical approach, emphasising the often-unacknowledged social arrangements that are co-produced with the technical elements of energy systems. Six diverse sociotechnical visions were developed and appraised: business as usual, large-scale technologies, deliberative energy society, smart tech society, local energy partnerships and off-grid energy communities. Across the five groups, we find a variety of problem framings that go far beyond the energy 'trilemma' and a greater diversity and range of technical and social criteria with which low-carbon energy futures are appraised. Our DDM study involving citizens and specialists shows that incumbent visions of centralised energy systems, such as business as usual and large-scale technologies, perform much lower than decentralised alternatives, such as a smart-tech society and local energy partnerships. Rather than a dominant focus on eliciting the views of 'representative' mini-publics to inform centralised decisions made by those managing 'the transition', DDM reveals and can support much more distributed modes of governing and democratising sustainable energy futures, across spaces and scales.